Cardiorespiratory fitness levels and associations with physical activity and body composition in young South African adults from Soweto - A. Prioreschi; S. Brage; K. Westgate; S. A. Norris; L. K. Micklesfield (BMC, 2017)
Abstract Background This observational study aims to describe fitness, and objectively measured physical activity levels and patterns in 409 young black South African adults (aged 19-20 years) from Soweto, as well as to examine associations between physical activity, fitness and BMI. Methods A sub-maximal ramped step test was used to obtain an estimate of maximal oxygen uptake (VO2max). Physical activity was measured using ActiGraph (GT1M) for 7 days in 256 participants. Time spent in sedentary (<100 counts per minute (cpm)), moderate (2020-5998 cpm) and vigorous (≥5999 cpm) intensity activity was calculated, and 90% of participants were considered active. Data are presented as mean(CI) or median(CI). Results Overweight and obesity was more prevalent in females than males (35% vs 8%, p < 0.001). Males had a higher VO2max than females (41.9(41, 43) vs 32.6(32, 33)mlO2/kg/min, p < 0.001); spent more time in moderate to vigorous intensity physical activity (MVPA) (83(80, 94) vs 43(38, 45)min/day, p < 0.001), and less time in sedentary behaviours (541(541, 567) vs 575(568, 597)min/day, p < 0.01). Sedentary time was not associated with VO2max, however BMI was inversely associated, and MVPA was positively associated, with VO2max (both p < 0.001). Conclusions The majority of young South African adults in this study were sufficiently active, and higher MVPA was associated with fitness. However, the high level of sedentary behaviour in this population is of concern and may be contributing to the increasing prevalence of overweight and obesity in this population. Young South African females are at greatest risk for decreased cardiovascular fitness and should be the focus for future interventions.